2015
DOI: 10.1021/acs.organomet.5b00206
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Amido-Digermynes, LGeGeL (L = Bulky Amide), toward Olefins and Related Molecules: Facile Reduction, C–H Activation, and Reversible Cycloaddition of Unsaturated Substrates

Abstract: Reactions of two sterically hindered amidodigermynes, L*GeGeL* (1; L* = −N(Ar*)(SiMe 3 ); Ar* = C 6 H 2 Me{C(H)Ph 2 } 2 -4,2,6) and L † GeGeL † (2; L † = −N(Ar † )-(SiPr i3 ); Ar † = C 6 H 2 Pr i {C(H)Ph 2 } 2 -4,2,6), with a variety of olefins and related molecules are investigated. These lead to the facile reduction, C−H activation, dehydrogenation, and/or cycloaddition of the unsaturated substrate. Specifically, reaction of L † GeGeL † with ethylene proceeds via a formal [2 + 2 + 2] cycloaddition to give th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 54 publications
2
48
0
Order By: Relevance
“…In av ery recent study,J ones and coworkers found that the amido-digermynes also reactw ithv arious unsaturated substrates, such as olefins, dienes,a lkynes, and PhNNPh. [16] Similarities and differences among the reactions of amido-and aryl-substituted digermynes with unsaturated species were also discussed. Scheme 1s hows the reaction products for the addition of 1,4-cyclooctadiene (COD) and propyne to L + GeGeL + .T he product of the former reaction agrees with af ormal [2+ +2] cycloaddition of aC =Cb ond to aG e-Ge multiple bond,w hich, according to the WoodwardHoffman rules, is as ymmetry-forbidden process.…”
Section: Introductionmentioning
confidence: 99%
“…In av ery recent study,J ones and coworkers found that the amido-digermynes also reactw ithv arious unsaturated substrates, such as olefins, dienes,a lkynes, and PhNNPh. [16] Similarities and differences among the reactions of amido-and aryl-substituted digermynes with unsaturated species were also discussed. Scheme 1s hows the reaction products for the addition of 1,4-cyclooctadiene (COD) and propyne to L + GeGeL + .T he product of the former reaction agrees with af ormal [2+ +2] cycloaddition of aC =Cb ond to aG e-Ge multiple bond,w hich, according to the WoodwardHoffman rules, is as ymmetry-forbidden process.…”
Section: Introductionmentioning
confidence: 99%
“…[17] In contrast, transition metal complexes often feature COTl igands with "semi-aromatic" character involving h n -hapticity (n = 2-5). [19] Ther eaction of COT with multiply bonded group 14 element systems Ar'MMAr' (M = Ge,S n; Ar' = 2,6-Ar 2 C 6 H 3 )y ielded the inverse-sandwich complexes (Ar'M) 2 (m 2 -h 2 :h n -COT)( M= Ge, n = 2; M= Sn, n = 3) featuring COT-ligands (with parameters associated with 10paromatic systems) that bridge two metal centers (Scheme 2, IV-M;M= Ge,Sn). [19] Ther eaction of COT with multiply bonded group 14 element systems Ar'MMAr' (M = Ge,S n; Ar' = 2,6-Ar 2 C 6 H 3 )y ielded the inverse-sandwich complexes (Ar'M) 2 (m 2 -h 2 :h n -COT)( M= Ge, n = 2; M= Sn, n = 3) featuring COT-ligands (with parameters associated with 10paromatic systems) that bridge two metal centers (Scheme 2, IV-M;M= Ge,Sn).…”
mentioning
confidence: 99%
“…[18] Examples of p-block metals featuring COT-derived ligands are rare. [19] Ther eaction of COT with multiply bonded group 14 element systems Ar'MMAr' (M = Ge,S n; Ar' = 2,6-Ar 2 C 6 H 3 )y ielded the inverse-sandwich complexes (Ar'M) 2 (m 2 -h 2 :h n -COT)( M= Ge, n = 2; M= Sn, n = 3) featuring COT-ligands (with parameters associated with 10paromatic systems) that bridge two metal centers (Scheme 2, IV-M;M= Ge,Sn). [20] In contrast, reaction with the group 13 digallene Ar'GaGaAr' forms an on-planar 1,5-cyclooctadiene-bridged bimetallic species (V), [21] demonstrating diver- We have recently shown that the dianionic bis(amidodimethyl)disiloxane ligands (abbreviated NON R ,R= tBu, Ar, Ar°= 2,6-(CHPh 2 ) 2 -4-tBuC 6 H 2 )w ill stabilize low oxidationstate bismuth [22] and indium species.…”
mentioning
confidence: 99%
“…R N1 -Ge Ge-R N1 12 also reacts with COT to form as andwich cycloocatatetraenediyl complex that is similar to 29,but thermally stable. [38]…”
Section: Activation Of Càcb Ondsmentioning
confidence: 99%